2021
DOI: 10.3389/fpls.2021.629733
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Application of 24-Epibrassinolide Reduces Chilling Injury Symptoms and Enhances Bioactive Compounds Content and Antioxidant Activity of Blood Orange Fruit

Abstract: Blood oranges (Citrus sinensis L. Osbeck cv. Sanguinello) fruit were treated with 24-epibrassinolide (Br) at 1, 5, and 10 μM previous to storage at 5°C during 42 days. The samples were analyzed after 14, 28, and 42 days plus 2 days at 20°C. Chilling injury was reduced in Br-treated fruit based on the lower percentage of electrolyte leakage and visual symptoms of peel dehydration and browning. Treated fruit showed lower acidity losses, due to retention of the main organic acids’ concentration (citric and malic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 45 publications
5
16
0
Order By: Relevance
“…Thus, there is a challenge for producers and the fruit industry to solve this problem. Postharvest treatments with elicitors could be useful approaches for enhancing the storability of blood oranges at cold temperatures (17). In recent years, postharvest treatments with elicitors compounds maintained antioxidant activity and bioactive compounds of blood oranges fruit during cold storage (2,17,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, there is a challenge for producers and the fruit industry to solve this problem. Postharvest treatments with elicitors could be useful approaches for enhancing the storability of blood oranges at cold temperatures (17). In recent years, postharvest treatments with elicitors compounds maintained antioxidant activity and bioactive compounds of blood oranges fruit during cold storage (2,17,20).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the postharvest application of elicitors has been applied for increasing storability and maintaining bioactive compounds of blood oranges fruit at prolonged cold storage (17). For the first time, the effect of postharvest treatment of GB was evaluated on maintaining the internal quality of blood orange fruit during cold storage.…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous postharvest applications of BRs have been reported to enhance bio-active compounds [ 34 , 35 , 36 , 37 ], delay ripening and senescence [ 35 ], and regulate defence-related enzymic activities, which develop robust defence mechanisms against different physiological disorders [ 34 , 35 , 37 , 38 , 39 ]. The mechanism of BRs further involves (1) the upregulation of membrane protein genes (leading to higher membrane integrity) [ 29 , 31 ], (2) the enhancement of phenylalanine ammonia lyase (PAL) and suppressed polyphenol oxidase (PPO) enzymatic activities, leading to higher phenol and anthocyanins accumulation [ 39 , 40 , 41 , 42 ], and (3) higher arginine pathway activity, leading to higher polyamines and proline accumulation [ 39 , 43 , 44 ], resulting in the improved antioxidant capacity of the crop.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, herein ( Figure 8), EBR induced phenolic biosynthesis and increased fruit antioxidant capacity in peach (Gao et al, 2016). However, in other studies, brassinosteroids were found to prevent antioxidants' losses rather than eliciting their accumulation (Habibi et al, 2021). In other vegetables such as eggplant, EBR led to opposite results and arrested phenolics biosynthesis through phenylalanine ammonia‐lyase (PAL) inhibition (Gao et al, 2015).…”
Section: Discussionmentioning
confidence: 91%
“…Wang et al (2012) working in green pepper showed that the most effective treatment consisted of 20 min dips at 20°C with 15 μM brassinolide. In eggplant and blood orange, also treatments at 10 μM were used to ameliorate CI symptoms and 6 μM in the tomato (Aghdam et al, 2012; Habibi et al, 2021), whereas such relatively high concentration induced positive results in some products, in other situations accelerated senescence (Rao et al, 2002; Vardhini & Rao, 2002). In the present work, we found that a single prestorage spray at doses 10–100 times lower than that reported for postharvest use in other crops, markedly reduced CI incidence (ca.…”
Section: Discussionmentioning
confidence: 99%